Natural Number Multiplication is Associative/Proof 2

From ProofWiki
Jump to navigation Jump to search


The operation of multiplication on the set of natural numbers $\N$ is associative:

$\forall x, y, z \in \N: \paren {x \times y} \times z = x \times \paren {y \times z}$


We are to show that:

$\left({x \times y}\right) \times n = x \times \left({y \times n}\right)$

for all $x, y, n \in \N$.

From the definition of natural number multiplication, we have that:

\(\displaystyle \forall m, n \in \N: \ \ \) \(\displaystyle m \times 0\) \(=\) \(\displaystyle 0\)
\(\displaystyle m \times \left({n + 1}\right)\) \(=\) \(\displaystyle \left({m \times n}\right) + m\)

Let $x, y \in \N$ be arbitrary.

For all $n \in \N$, let $P \left({n}\right)$ be the proposition:

$\left({x \times y}\right) \times n = x \times \left({y \times n}\right)$

Basis for the Induction

$P \left({0}\right)$ is the case:

\(\displaystyle \left({x \times y}\right) \times 0\) \(=\) \(\displaystyle 0\)
\(\displaystyle \) \(=\) \(\displaystyle x \times 0\)
\(\displaystyle \) \(=\) \(\displaystyle x \times \left({y \times 0}\right)\)

and so $P \left({0}\right)$ holds.

This is our basis for the induction.

Induction Hypothesis

Now we need to show that, if $P \left({k}\right)$ is true, where $k \ge 0$, then it logically follows that $P \left({k + 1}\right)$ is true.

So this is our induction hypothesis:

$\left({x \times y}\right) \times k = x \times \left({y \times k}\right)$

Then we need to show:

$\left({x \times y}\right) \times \left({k + 1 }\right) = x \times \left({y \times \left({k + 1}\right)}\right)$

Induction Step

This is our induction step:

\(\displaystyle \left({x \times y}\right) \times \left({k + 1 }\right)\) \(=\) \(\displaystyle \left({\left({x \times y}\right) \times k}\right) + \left({x \times y}\right)\) Definition of Natural Number Multiplication
\(\displaystyle \) \(=\) \(\displaystyle \left({x \times \left({y \times k}\right)}\right) + \left({x \times y}\right)\) Induction Hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \left({x \times y}\right) + \left({x \times \left({y \times k}\right)}\right)\) Natural Number Addition is Commutative
\(\displaystyle \) \(=\) \(\displaystyle x \times \left({y + \left({y \times k}\right)}\right)\) Natural Number Multiplication Distributes over Addition
\(\displaystyle \) \(=\) \(\displaystyle x \times \left({\left({y \times k}\right) + y}\right)\) Natural Number Addition is Commutative
\(\displaystyle \) \(=\) \(\displaystyle x \times \left({y \times \left({k + 1 }\right)}\right)\) Definition of Natural Number Multiplication

So $P \left({k}\right) \implies P \left({k + 1}\right)$ and the result follows by the Principle of Mathematical Induction.